Accuracy of the dental pulp sensibility test using cold spray for the diagnosis of pulp diseases: an observational clinical study - Matos, Felipe de Souza (2021)
The dental pulp sensibility test is one of the main auxiliary resources for the diagnosis of pulp pathologies, and its accuracy is still debatable. This cross-sectional observational study evaluated the accuracy of the pulp sensibility test (PST) using cold spray (1,1,1,2-tetrafluoroethane) for the diagnosis of pulp diseases and determined the effect of individual and clinical variables on the reliability of this test. The paper was designed following the STROBE statement. Sixty patients with indications for primary endodontic treatment were selected and examined from August 2017 to July 2018. Data collection was performed through interviews, clinical/radiographic examinations and the PST. The results of the cold test, along with data on sex, age, the tooth type regarding the root number, and the presence of restorations and caries, as well as the recent consumption of analgesics, were recorded. The presence of bleeding within the pulp chamber was used as the gold standard to compare with the clinical diagnosis and to identify the true-positive, false-positive, true-negative, and false-negative responses. The accuracy of PST achieved in subgroups of individual and clinical variables was compared using the chi-square test with a significance level of 5% (p < 0.05). The PST with the use of cold spray showed a sensitivity of 0.88, a speciﬁcity of 1.00, a positive predictive value of 1.00, a negative predictive value of 0.86, and an accuracy of 0.93. The accuracy of the cold spray was not affected by individual or clinical variables. The PST with the use of cold spray is an accurate and reliable method for determining the diagnosis of pulp diseases, especially in cases of pulp vitality or irreversible pulpitis.